2013
DOI: 10.1016/j.apm.2012.10.017
|View full text |Cite
|
Sign up to set email alerts
|

An improved solution to the replenishment policy for the EMQ model with rework and multiple shipments

Abstract: a b s t r a c tRecently, [1] present an alternative optimization procedure to derive the optimal replenishment lot size for an economic manufacturing quantity (EMQ) model with rework and multiple shipments. This inventory model was proposed by Chiu et al. (2011) [2]. Both papers do not consider the determining of the number of shipments. This paper determines both the optimal replenishment lot size and the optimal number of shipments jointly. The solution of this paper is better than the solutions of Chiu et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…Kim et al [37] derived a model for multi-stage production system considering defective items. Similarly, Cárdenas-Barrón et al [38] developed an EMQ model for imperfect production associated with rework and multiple shipment strategies. Sarkar et al [39] derived an economic manufacturing quantity (EMQ) model under the effects of reliability and inflation.…”
Section: Literature Review and Research Gapmentioning
confidence: 99%
“…Kim et al [37] derived a model for multi-stage production system considering defective items. Similarly, Cárdenas-Barrón et al [38] developed an EMQ model for imperfect production associated with rework and multiple shipment strategies. Sarkar et al [39] derived an economic manufacturing quantity (EMQ) model under the effects of reliability and inflation.…”
Section: Literature Review and Research Gapmentioning
confidence: 99%
“…More recent studies can be found in Diponegoro and Sarker (2006), Ben-Daya, Darwish, and Ertogral (2008) and Mungan, Yu, and Sarker (2010). Improved solution procedures to compute the discrete lot size can be found in Cárdenas- Teng (2011), Cárdenas-Barrón et al (2012) and Cárdenas-Barrón, Sarkar, and Treviño-Garza (2013). These works have focused on the optimal EPQ strategy by either excluding the delivery policies, or assuming that the delivery quantity is fixed or known beforehand.…”
Section: Introductionmentioning
confidence: 96%
“…In this model carbon foot print and carbon emission costs were considered witout any energy consideration. Cárdenas-Barrón et al [25] developed the benefit of multi-shipment in an economic manufacturing model without having any concept of energy matter. Giotitsa et al [26] strives an appropriate approach for production of energy and its distribution.…”
Section: Introductionmentioning
confidence: 99%